The collected writings of John Maynard Keynes, Volume 15, Activities 1906-1914: India and Cambridge - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
This volume, containing papers written by Keynes, in the course of his various activities, is chiefly concerned with his work down to the outbreak of war in 1914 on problems of Indian currency and especially with the part that he played in influencing and shaping the report of the (Austen Chamberlain) Royal Commission on Indian Finance and Currency. The papers show the young Keynes (he was under 30 when appointed) with a complete mastery not only of the broad and academic principles but also, as throughout his life, of the details, holding his own in debate with the acknowledged authorities and securing his main objectives, thanks largely to his indefatigable capacity for quick yet elegant and lucid draftsmanship. This volume is a necessary companion to his own Indian Currency and Finance (Volume 1 in this series)